Family physicians' awareness and general knowledge of hidradenitis suppurativa: A survey research. Issue 7 (5th April 2021) - Esme, Pelin; Akoglu, Gulsen; Sari, Oktay; Caliskan, Ercan
Abstract: Rationale, aims, and objective: Medical consultations of family physicians play a key role in early diagnosis and proper management of hidradenitis suppurativa (HS). This study aimed to investigate family physicians' disease awareness, general attitudes, and knowledge of HS. Material‐Methods: This cross‐sectional descriptive study was conducted with 211 family physicians and residents through a web‐based survey. The questionnaire consisted of 25 questions about the demographic characteristics of the participants as well as their awareness and general knowledge of HS. Results: While 90% of physicians know that the diagnosis of HS is made clinically without any need for a laboratory examination,  only 23.7% of them felt confident performing such a diagnosis. About 63% of participants defined HS as an infectious disease of the apocrine glands, contradictive to the real pathophysiology. About 21% of them had not been medically trained in HS, and 3% of them even had never heard the name of HS. Only 33% were aware of the role of biological agents. Most of the family physicians (57.4%) were willing to participate in postgraduate education programmes about HS. Conclusion: The family physicians' awareness of HS is limited. Increased practice in medical education and postgraduate education programmes may help increase the knowledge of family physicians.